Answer:
Simplifying
6(2x + -1) = 4 + 7x
Reorder the terms:
6(-1 + 2x) = 4 + 7x
(-1 * 6 + 2x * 6) = 4 + 7x
(-6 + 12x) = 4 + 7x
Solving
-6 + 12x = 4 + 7x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-7x' to each side of the equation.
-6 + 12x + -7x = 4 + 7x + -7x
Combine like terms: 12x + -7x = 5x
-6 + 5x = 4 + 7x + -7x
Combine like terms: 7x + -7x = 0
-6 + 5x = 4 + 0
-6 + 5x = 4
Add '6' to each side of the equation.
-6 + 6 + 5x = 4 + 6
Combine like terms: -6 + 6 = 0
0 + 5x = 4 + 6
5x = 4 + 6
Combine like terms: 4 + 6 = 10
5x = 10
Divide each side by '5'.
x = 2
Simplifying
x = 2
Explanation: